(untitled) (Swiss Medical Weekly, 2018)
The relevance of genetic and epigenetic alterations in the pathogenesis of inflammatory bowel disease (IBD) is still poorly understood. So far, 240 risk gene loci have been associated with IBD. They are mainly involved in regulating innate and adaptive immunity, as well as maintaining intestinal epithelial barrier function. However, the functional consequences of the identified genetic polymorphisms for IBD pathogenesis in vivo are often unknown. Even less is known about the role for epigenetic modifications in IBD pathogenesis. Though a number of epigenetic events seem to be causatively involved IBD pathogenesis, our knowledge about the functional relevance of those epigenetic modifications is scanty. This opens up a broad research field that generates novel insights into the pathophysiology of intestinal and chronic inflammatory disease. Patterns of DNA methylation and histone modifications might serve not only as biomarkers of disease activity or disease course, but also as new targets in therapeutic interventions in IBD patients.